Computational and experimental analysis of machine tool vibrations in micro-milling - Sagris, Dimitrios; Davids, Constantine; Stergianni, Evlampia; Tsiafis, Christos; Tsiafis, Ioannis (MATEC web of conferences, 2017)
In machining processes, it is necessary to study the vibration phenomena which take place in cutting zone between the cutting tool and the workpiece in order to ascertain the factors that affect them. The subject of this paper is to identify the influence of the cutting parameters and the dynamic characteristics of the machine tool spindle and the cutting tool on the vibrations by means of FEM analysis. A FEM modal analysis of the machine tool spindle in combination with cutting force measurements are used to build up a transient FEM model in time domain in order to study the vibrations induced by the cutting process. The results of the transient FEM model will serve for further analysis to find out the optimum cutting parameters in micro-milling.